2017
DOI: 10.1055/s-0037-1602658
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Intrapartum Fetal Head Compression: What Is the Impact on the Fetal Brain?

Abstract: Objective During labor the fetal head is subjected to pressure related to uterine contractions and maternal pushing. Here we systematically review what is known about fetal head compression and its effects on fetal intracranial pressure, oxygenation, blood flow and cerebral function, and the plausibility that it might cause isolated fetal brain injury. Study Design Systematic review of intrapartum fetal head compression and fetal brain injury in accordance with the MOOSE methodology. The PubMed database was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This is not consistent with the observation of clinicians who had experience of the British system for almost four decades before 2007 (Figures 4-6) [3,[24][25][26][27]. Headcompression decelerations are not associated with cerebral ischemia or anoxia and hence are due to benign reflex mechanisms [33]. The claim that early decelerations must be "gradual" has been shown to be posttruth ideology [3].…”
Section: Myth No 2 Myth: "True" Early Decelerations Are Very Rarementioning
confidence: 89%
“…This is not consistent with the observation of clinicians who had experience of the British system for almost four decades before 2007 (Figures 4-6) [3,[24][25][26][27]. Headcompression decelerations are not associated with cerebral ischemia or anoxia and hence are due to benign reflex mechanisms [33]. The claim that early decelerations must be "gradual" has been shown to be posttruth ideology [3].…”
Section: Myth No 2 Myth: "True" Early Decelerations Are Very Rarementioning
confidence: 89%
“…There is considerable controversy about the role of head compression as a cause of FHR decelerations and of adverse perinatal outcome, as one would expect when any new approach is introduced that challenges embedded dogma or recalls neglected science. Some doubt its existence [94]; others reject its pertinence to clinical outcomes, except perhaps in the most extreme circumstances [38]; others focus on its medico-legal implications [95] [96], and some advise caution before rejecting the notion [97].…”
Section: The Head Compression Controversymentioning
confidence: 99%
“…Light and moderate configurations do not lead to pathological changes but expressed (pathological) degree leads to compression hypoxia of the fetal brain [7] and birth trauma. Clinical and experimental studies have shown that head compression leads to deceleration of cardiac activity [8][9][10]. When does a pathological head configuration occur?…”
Section: Types and Degree Of Configurationmentioning
confidence: 99%